IRRIGATION MANAGEMENT IN SOYBEAN CROPS INFLUENCES THE OCCURRENCE OF NEMATODES IN THE SOIL - Gava, Ricardo; Silva, Thiago Ramos da; Cotrim, Mayara Favero [UNESP]; Lima Abreu, Alexandra Botelho; Anselmo, Jefferson Luis; Teodoro, Paulo Eduardo (Univ Federal Uberlandia, 2020)
One of the main limitations of soybean production is related to water availability and organisms found in the soil. Under the hypothesis that soil moisture may influence the nematode population, this study aimed to verify the occurrence of nematodes associated with different irrigation management in soybean crops. The experiment was carried out in a randomized block design. Treatments consisted of a subplot scheme, with four replications. The plots consisted of ten irrigation managements divided into five irrigation frequencies (1,2,3,4, and 5 days) and five additional water depths (25, 50, 75, 100, and 125% of crop evapotranspiration - Etc). The subplots were composed of four different soybean cultivars (NA 5909 RR, AS 3680 IPRO, and Desafio RR ePower IPRO). The experiment analyzed the variables plant height, first pod insertion, number of plants, moisture, hundred-grain weight, yield, and occurrence of nematode eggs and adults. Nematodes influence all the production components analyzed, affecting mostly the hundred-grain weight, especially the nematode Helicotylenchus sp., although the Meloidogyne sp. population was larger. The phytonematode population reduces with the increase in soil moisture to levels close to the saturation, indirectly influencing the yield increase.
Keywords: Phytonematode; Glycine Max L; Water depths